The effect of glycerol on signal supression during electrospray ionization analysis of proteins. Issue 2 (2004) - Mendes Mendes, M. A. M. A.; Souza Souza, B. M. B. M.; Marques Marques, M. R. M. R.; Palma Palma, M. S. M. S.
Abstract : The effect of salts, detergents and chaotropic agents on mass spectrometric analysis are relatively well understood, mainly due to their actions decreasing the performance of ESI interface in mass spectrometric analysis. However, there are few studies in the literature characterizing the effect of protein stabilization by glycerol, followed in some circumstances by the suppression of protein signal when ESI interface is used. The aim of the present research was to investigate in details the mass spectrometric behavior of some proteins in presence of high levels of glycerol during ESI–MS analysis. Thus, horse heart myoglobin and chicken ovalbumin were used as standard proteins. It was demonstrated that the presence of 1% (v/v) glycerol suppressed the signal of these proteins during the ESI–MS analysis, even when the sample nozzle potential was scanned from 28 to 80 V. However, when the glycerol concentration was decreased to 0.5% (v/v) and the sample cone voltage adjusted to 50 V, a perfect envelope of peaks was observed, allowing the spectrum deconvolution and the molecular mass determination with mass accuracy lower than 0.01% in each situation. A molecular explanation for this suppressive effect and for the analytical overcoming of this difficult is proposed.